2015
DOI: 10.1007/s40474-015-0048-4
|View full text |Cite
|
Sign up to set email alerts
|

Training Parents of Children with Intellectual Disabilities: Trends, Issues, and Future Directions

Abstract: This review summarizes selected studies involving education and training programs designed to improve parents' ability to provide research-based support and intervention for their children with intellectual disabilities. First, we highlight stressors and obstacles associated with parenting a child with intellectual disability and note the relative paucity of existing research in light of the increased risk of stress, anxiety, and depression reported for this population. Next, we provide a description of recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 94 publications
0
41
0
2
Order By: Relevance
“…From another point of view, mothers of CWDs frequently express a need for advice on how to promote the development of their children and how to interact with them, regardless of the family characteristics and the type/severity of the child's disability (Bailey & Simeonsson, 1988;Bailey, Blasco, & Simeonsson, 1992;Bailey et al, 1999). There have been substantial studies reporting that parents who participate in parent training programs gain various benefits in terms of their ability to teach new skills, to cope with problematic behaviors, to reduce stress and to use positive behavior support strategies (Feldmen & Werner, 2002;Machalicek et al, 2015;McIntyre, 2008;Meadan, Ostrosky, Zaghlawan, & Yu, 2009). To the best of our knowledge, however, there has been only one study to date, including a training program for the parents of CWID and investigating the effects of the program on family home quality (Bennet & Algozzine, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From another point of view, mothers of CWDs frequently express a need for advice on how to promote the development of their children and how to interact with them, regardless of the family characteristics and the type/severity of the child's disability (Bailey & Simeonsson, 1988;Bailey, Blasco, & Simeonsson, 1992;Bailey et al, 1999). There have been substantial studies reporting that parents who participate in parent training programs gain various benefits in terms of their ability to teach new skills, to cope with problematic behaviors, to reduce stress and to use positive behavior support strategies (Feldmen & Werner, 2002;Machalicek et al, 2015;McIntyre, 2008;Meadan, Ostrosky, Zaghlawan, & Yu, 2009). To the best of our knowledge, however, there has been only one study to date, including a training program for the parents of CWID and investigating the effects of the program on family home quality (Bennet & Algozzine, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, parent involvement was generally addressed in the parent training programs aiming to teach parents how to teach their children and how to prevent or decrease problem behaviors of their CWDs. The studies evaluating the effectiveness of parent programs are mostly concerned about the outcomes related to parents and children (Machalicek, Lang, & Raulston, 2015;Matson, Mahan, & LoVullo, 2009;McIntyre, 2008McIntyre, , 2013; but not the quality of the home environment. Taking into account that the quality of the home learning environment has significant effects on the development of children and its effects continue until age 16 (Taggart et al, 2015), and what parents do with their child is important, as much as their education, income and other characteristics (Sylva, Melhuish, Sammons, Siraj-Blatchford, & Taggart, 2004), it seems worth investigating the involvement of parents of CWDs in home learning activities and the available toys at their home.…”
mentioning
confidence: 99%
“…Due to the low rates of homework completion, it was not possible to compare participant characteristics or response to intervention for those who did complete homework and those who did not. Low parental input may have influenced the results of this study, as children with ID often have difficulties generalizing concepts and would require assistance to do so (Machalicek, Lang, & Raulston, ). Thus while some improvements were seen in the participants’ anxiety based upon teacher reports, it is possible that these changes did not generalize to situations outside of the school or classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Vismara et al ( 2012 ) found in their study that the parents of nine toddler-aged children with ASD were successful in learning a parenting intervention programme through telehealth provision, comprising of a DVD learning module and 12 weekly video-conferencing sessions. As many telehealth provisions are available for free, providing treatment or parent-training through telehealth can be cost-effective (Machalicek et al 2015 ). Furthermore, the use of telehealth may help the treatment programme to reach out to a greater number of families over a greater distance (Vismara et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%